2017
DOI: 10.1186/s40413-017-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

A 17-year-old male with a Small Bowel Neuroendocrine Tumor: flushing differential diagnosis

Abstract: BackgroundNeuroendocrine tumors (NETs) are heterogeneous neoplasms that originate from cells with a secretory function. Small bowel NETs (SB-NETs) are related to serotonin hypersecretion which causes: flushing, diarrhea, abdominal pain, bronchoconstriction and heart involvement, also known as carcinoid syndrome (CS). CS can be confused with an allergic reaction and thus should be considered as a differential diagnosis in the allergy consult. We present the case of a pediatric patient initially referred under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition to these symptoms, it has been reported that approximately half of individuals with CS will develop carcinoid heart disease (CHD), a potentially life-threatening complication [6, 9]. Although the exact pathophysiology of CHD is not well understood, the secretion of hormones and other products from tumours is suspected to lead to the deposition of cardiac plaques, which are primarily found on the right side of the heart (∼90% of cases) [1, 10]. There is currently a lack of consensus regarding the diagnosis, management, and preventative measures for CHD, despite patients having significantly worse life expectancy than those with CS alone [1, 6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these symptoms, it has been reported that approximately half of individuals with CS will develop carcinoid heart disease (CHD), a potentially life-threatening complication [6, 9]. Although the exact pathophysiology of CHD is not well understood, the secretion of hormones and other products from tumours is suspected to lead to the deposition of cardiac plaques, which are primarily found on the right side of the heart (∼90% of cases) [1, 10]. There is currently a lack of consensus regarding the diagnosis, management, and preventative measures for CHD, despite patients having significantly worse life expectancy than those with CS alone [1, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Cyanotic flushing associated with a burning sensation lasting no more than 1 min is associated with midgut tumors. Tumors with anterior location cause generalized pruritus ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…An illustrative case is a 35-year-old Hispanic woman from South Texas who suffered from undiagnosed carcinoid syndrome for over a decade, which eventually progressed to severe carcinoid heart disease. Initially, her symptoms were misattributed to more common cardiac conditions, delaying appropriate treatment [9]. This case highlights the necessity for cardiologists to consider carcinoid syndrome in patients presenting with unusual cardiac symptoms like tricuspid regurgitation or right-sided heart failure, particularly when accompanied by systemic symptoms like flushing or diarrhea.…”
Section: Cardiac Involvement Endocrine and Hormonal Effects And Other...mentioning
confidence: 96%
“…Further workup found the cause to be a carcinoid tumor manifesting from the patient's right ovary [9]. While the gastrointestinal symptoms associated with carcinoid syndrome, such as abdominal pain, vomiting, and persistent diarrhea, are welldocumented, their prevalence among younger patients remains understudied.…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%